Classificatory aspects of the Constitution (Revista do Tribunal Regional Federal da 3ª Região, 2020)
The current article deals about the classificatory aspects of the term Constitution, approaching issues related to its multiple concepts, as well as its various classifications and the intrinsic association of the origin and history of constitutional law with the emergence and evolution of the state.
Keywords: Constitution; Constitutional Law; State